Cross-Section Calculations for Electron-Impact Ionization of Pyrimidine Molecule and Its Halogenated Derivatives: 2-Chloropyrimidine, 5-Chloropyrimidine, 2-Bromopyrimidine and 5-Bromopyrimidine - Bożena Żywicka; Paweł Możejko (Molecules)
The total cross-sections for the single electron-impact ionization of pyrimidine (C4H4N2), 2-chloropyrimidine (2-C4H3ClN2), 5-chloropyrimidine (5-C4H3ClN2), 2-bromopyrimidine (2-C4H3BrN2) and 5-bromopyrimidine (5-C4H3BrN2) molecules have been calculated with the binary-encounter-Bethe model from the ionization threshold up to 5 keV. The input data for the BEB calculations concerning electronic structure of the studied targets have been obtained with quantum chemical methods including the Hartree–Fock (H-F) and the outer valence Green function (OVGF) methods. The calculated cross-section for the ionization of the pyrimidine molecules due to electron impact is compared with available experimental and theoretical data. The question of the magnitude the pyrimidine ionization cross-section is also discussed, as is the efficiency of the ionization process of studied halogenated derivatives of pyrimidine.